Turbulence underneath the big calm? Exploring the micro-evidence behind the flat trend of manufacturing productivity in Italy - Giovanni Dosi; Marco Grazzi; Chiara Tomasi; Alessandro Zeli (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2010)
Italy ranked last in terms of manufacturing productivity growth according to OECD estimates over the last decade with a flat, if not declining, trend. In this work we investigate the underlying firm-level dynamics of enterprises on the grounds of a database developed by the Italian Statistical Office (ISTAT) covering the period 1989-2004 and containing information on more than 100,000 firms. Over the period not only the indicators of central tendency of the distribution of labour productivities have not significantly changed, but also the whole sectoral distributions have remained relatively stable over time, with their support at least not shrinking or even possibly widening over time. This is even more surprising if one takes into consideration the Euro shock that occurred during the period of investigation. On the contrary we observe that inter-decile differences in productivity have been increasing. Further, heterogeneous firms' characteristics (i.e. export activity and innovativeness) appear to have contributed to boost such intraindustry differences. Given such wide heterogeneities we resort to quantile regressions to identify the impact of a set of regressors at different levels of the conditional distribution of labor productivity. One phenomenon that we observe is what we call a tendency toward neo-dualism involving the co-existence of a small group of dynamic firms with a bigger ensemble of much less technologically progressive ones.
Keywords: 330